The influence of American mink odour on the spatial distribution and behaviour of water voles. (7th August 2019) - Brzeziński, Marcin; Pyrlik, Joanna; Churski, Marcin; Komar, Ewa; Zalewski, Andrzej
Abstract: The perception and assessment of predation risk often cause changes in the activities of animals and induce behavioural responses that may in turn affect their movements and distribution. To simulate high predation risk in a midfield pond riparian habitat, we used fresh faeces from ranch American mink Neovison vison and recorded behavioural responses of water voles Arvicola amphibius . In areas where mink odour was deployed, the numbers of captured vole individuals and their trappability were significantly lower than in control areas. Several voles migrated from the zones with deployed mink faeces to the areas without faeces, thus proving that increased predation risk affects the distribution of individuals in a population. The response to mink odour was much more pronounced in females than in males; in areas with deployed mink faeces, not a single female was trapped. We conclude that although American mink is a non‐native, invasive predator, water voles respond to mink odour by reducing their activity and/or by avoiding places with higher predation risk.